Consumers’ Social Responsibility in the Process of Energy Consumption—The Case of Poland - Kinga Hoffmann-Burdzińska; Agata Stolecka-Makowska; Olaf Flak; Marcin Lipowski; Mariusz Łapczyński (Energies, 2022)
Although European energy policy supports the reduction of energy consumption, the current economic and political situation in Poland and uncertainty related to the origin of energy sources do not support it. Therefore, the aim of this paper is to identify and assess the factors that affect the energy-saving behaviour of Polish consumers in the process of energy consumption. The research problem concerns the specificity of behaviours that are part of new trends in consumption, such as greening and the ethical dimension of consumption. The research question arises as to what the social responsibility of consumers is in the process of energy consumption. The research problem comes down to the question of factors that determine the behaviour of an individual consumer in the energy market. In order to realise the indicated purpose of the article, a conceptual research model was built and direct research was conducted using the research method, which was an online survey (CAWI). The research was run among 1422 individual consumers. After verifying 14 research hypotheses, it can be concluded that energy-saving behaviour is influenced in similar ways by a set of factors. In the paper there are findings which show that the generally understood energy-saving behaviour (Y1—at home and Y2—off-site) is influenced by the following factors: X1—energy-saving knowledge, X3—green consumer values, X5—social influence, X6—beliefs, and X7—consumer awareness. The specific mechanism of influence of each of the dominant factors is that the higher the intensity of these factors in consumer behaviour, the more actions are taken to save energy inside or outside the home. However, X2—energy-saving cost perception and X4—materialism presents this influence mechanism only for Y1—energy-saving behaviour at home.